A Systematic Literature Review of the Development of Technology-Based History Learning (2022–2026) - Wafa Kamila; Indah Ramadani; Irfan Swanto Yusni; Syarifuddin Syarifuddin; Rani Oktapiani (Universitas Negeri Semarang, 2026)
This study aims to analyze the development of research on technology-based history learning through a Systematic Literature Review (SLR) approach. The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines by reviewing 93 articles indexed in the Scopus database published between 2022 and 2026. The data were analyzed using VOSviewer software to map research trends, country distribution, institutional affiliations, journals, authors, and keyword occurrences in the field of history learning. The findings indicate that publications on technology-based history learning have increased significantly, reaching their peak in 2025, with Indonesia emerging as the leading contributor. The most frequently occurring keywords include history learning, history education, historical thinking, and e-learning. Furthermore, the study reveals that the integration of technology into history learning has a positive impact on enhancing student engagement, critical thinking skills, and instructional innovation. These findings are expected to serve as a valuable reference for future research and the development of technology-based history learning practices. In conclusion, technology-based history learning has demonstrated increasingly strong development as a relevant field of study in contemporary education. The integration of technology not only enriches history teaching strategies but also has the potential to improve learning quality by strengthening students' engagement in historical thinking and fostering pedagogical innovation. Therefore, further research is needed to expand investigations into diverse contexts, methodologies, and technological applications in history learning.